Phosphorus cycling in Lake Cadagno, Switzerland: A low sulfate euxinic ocean analogue. (15th April 2019) - Xiong, Yijun; Guilbaud, Romain; Peacock, Caroline L.; Cox, Raymond P.; Canfield, Donald E.; Krom, Michael D.; Poulton, Simon W.
Abstract: Low sulfate, euxinic water-column conditions were a common feature of many Precambrian and Phanerozoic periods of ocean anoxia. The cycling of phosphorus in anoxic marine environments exerts a fundamental control on primary productivity, organic carbon production and burial, and hence ultimately oxygen production, but the dynamics of the phosphorus cycle in low sulfate, euxinic settings are largely unknown. Here, we provide a detailed geochemical investigation of phosphorus cycling in the low sulfate, euxinic Lake Cadagno, Switzerland, which is considered a prime analogue for ancient euxinic oceans. We find evidence for extensive recycling of phosphorus from the sediments back to the water column, stimulated by the microbial release of phosphorus from organic matter and Fe (oxyhydr)oxide minerals. Consistent with previous studies of modern and ancient anoxic settings, this regenerated flux maintains high concentrations of phosphorus in the water column, thus promoting a positive productivity feedback. However, the low-sulfate condition of the overlying water column, combined with the rapid removal of sulfide (as pyrite) from porewaters, promotes formation of Fe(II) phosphate minerals (e.g., vivianite) close to the sediment-water interface. This, in turn, modulates the extent of phosphorus recycling back to the water column, and contrasts with modern fully marine euxinic settings, where the higher concentrations of dissolved sulfate promote sulfide formation to greater depths, thus limiting Fe(II) phosphate formation close to the sediment-water interface. The prevalence of low-sulfate conditions during past euxinic episodes suggests that the operation of this near-surface sedimentary trap for recycled phosphorus would have limited the positive P-driven productivity feedback, promoting only a moderate degree of P recycling. Furthermore, the precise magnitude of this recycled P flux would, on a global scale, have been dependent on changes in the size of Earth's marine sulfate reservoir through time. Thus our findings have major implications for rates of P-driven productivity and organic carbon burial in ancient euxinic settings, which have not previously been factored into reconstructions of Earth's oxygenation history.